Case report: Prenatal diagnosis of fetal intracranial hemorrhage due to compound mutations in the JAM3 gene - Xu, Min; Jin, Pengzhen; Huang, Yingzhi; Qian, Yeqing; Lin, Miaochun; Zuo, Juan; Zhu, Jin; Li, Zhaohui; Dong, Minyue (Frontiers in Genetics, 2022)
Intracranial hemorrhage is a common complication in preterm infants but occasionally in fetus. Disruptions of the genes, such as the COL4A1 and COL4A2 gene, are common genetic causes identified in the fetal intracranial hemorrhage, however, the disruptions of the JAM3 gene are rarely reported. In the current investigation, fetal intracranial hemorrhage and dilated lateral ventricles were observed in three consecutive siblings in a pedigree. The pregnancies were terminated and whole-exome sequencing followed by Sanger sequencing was performed on the affected fetuses. Preimplantation genetic testing for monogenic disease was performed to avoid the recurrence. The compound heterozygous variants of c.712+2T>A and c.813C>G p.Tyr271* in the JAM3 gene (NM_032801.4) were identified in the proband and its affected brother, which were predicted to be pathogenic. The variant of c.813C>G p.Tyr271* but not c.712+2T>A was identified in the fourth fetus, implying a good prognosis. Our findings expanded the spectrum of pathogenic mutations in the JAM3 gene and revealed an important application of fetal whole-exome sequencing in idiopathic fetal intracranial hemorrhage.